MALDI-TOF MS Affords Discrimination of Deinococcus aquaticus Isolates Obtained From Diverse Biofilm Habitats - Tuohy, James M.; Mueller-Spitz, Sabrina R.; Albert, Chad M.; Scholz-Ng, Stacy E.; Wall, Melinda E.; Noutsios, George T.; Gutierrez, Anthony J.; Sandrin, Todd R. (Frontiers in Microbiology, 2018)
MALDI-TOF MS has been used routinely over the past decade in clinical microbiology laboratories to rapidly characterize diverse microorganisms of medical importance both at the genus and species levels. Currently, there is keen interest in applying MALDI-TOF MS at taxonomic levels beyond species and to characterize environmental isolates. We constructed a model system consisting of 19 isolates of Deinococcus aquaticus obtained from biofilm communities indigenous to diverse substrates (concrete, leaf tissue, metal, and wood) in the Fox River - Lake Winnebago system of Wisconsin to: 1) develop rapid sample preparation methods that produce high quality, reproducible MALDI-TOF spectra and 2) compare the performance of MALDI-TOF MS-based profiling to common DNA-based approaches including 16S rRNA sequencing and genomic diversity by BOX-A1R fingerprinting. Our results suggest that MALDI-TOF MS can be used to rapidly and reproducibly characterize environmental isolates of D. aquaticus at the subpopulation level. MALDI-TOF MS provided higher taxonomic resolution than either 16S rRNA gene sequence analysis or BOX-A1R fingerprinting. Spectra contained features that appeared to permit characterization of isolates into two co-occurring subpopulations. However, reliable strain-level performance required rigorous and systematic standardization of culture conditions and sample preparation. Our work suggests that MALDI-TOF MS offers promise as a rapid, reproducible, and high-resolution approach to characterize environmental isolates of members of the genus Deinococcus. Future work will focus upon application of methods described here to additional members of this ecologically diverse and ubiquitous genus.